Shear strengthening of R/C beams using AFRP sheet with anchored ends - Imran, Iswandi; Mujiman, Mujiman (2006)
Many studies have been conducted on the behaviour of beams shearstrengthened with FRP sheets. The studies show that FRP materials can produce good performance when used to carry some portion of shear force in the shear-strengthened beam. However, the performance of FRP sheets is found limited by bond capacity between FRP sheets and concrete surface. In certain case, anchorage system can be introduced to the FRP strengthening scheme to improve the bond performance. This paper presents experimental and analytical studies conducted to evaluate the contribution and behaviour of FRP sheets with anchored ends in strengthening the shear behaviour of reinforced concrete beams. In the study, nine reinforced concrete beam specimens were fabricated and tested. Test parameters of the study include thickness of FRP sheet used, types of wrap applied, type of anchors and diameter of anchor head used. Two types of anchorage system were proposed in the study, i.e. insert anchor system and C-embedded anchor system. The results from this study show that the proposed anchorage system can improve the contribution of FRP in carrying the shear force in beams. In addition, the Cembedded anchor system exhibits better performance than the insert anchor system. Lastly, the behaviour of beams strengthened using FRP stirrups with anchored end can be better predicted by the ACI 440 design equations for full-wrap scheme.